AB0150 Tocilizumab Does not Induce Apoptosis in Neutrophils in Vitro. (10th June 2014) - Witte, T.; Ulrich, S.; Buyny, S.; Schmidt, R.E.; Jacobs, R.
Abstract : Background: Tocilizumab is an inhibitor of the IL-6 receptor and is highly efficient in the treatment of rheumatoid arthritis. Leucopenia has been observed in 10% of the patients, which has been partly attributed to concomitant methotrexate therapy, but may also occur in monotherapy with tocilizumab. The pathomechanism of the leucopenia remains unclear. Objectives: To study the influence of tocilizumab on the function and on apoptosis of neutrophils. Methods: Granulocytes from the peripheral blood of 13 healthy controls were incubated overnight with medium only or with medium containing various concentrations between 0.8 and 800 μg/ml of tocilizumab. The concentrations were chosen based on the recommended dose of tocilizumab of 8 mg/kg. The apoptosis rate of the granulocytes was studied by Annexin-V/7-AAD staining using flow cytometry. In addition, the surface expression of the cell adhesion receptor CD11b, the chemokine receptors CD181 and CD182 and of CD62L, indicating an enhanced migration capacity, were measured. The adhesion of granulocytes to a layer of human vascular endothelial cells (HUVEC) after 1 hour of incubation was studied by harvesting and counting non-bound cells. Results: Tocilizumab was found to bind to neutrophils. The treatment of neutrophils with tocilizumab slightly reduced the expression of CD62L at the highest dose studied and almost doubled the adhesion to HUVEC in vitro in the whole dose range. The rate of apoptosis and of cell survival was not affected. Conclusions: Neutropenia during treatment with tocilizumab appears to be a consequence of enhanced cell adhesion to endothelia and presumably migration rather than of apoptosis and cell death. Acknowledgements: Chugai Pharma Marketing Ltd for financial support of the study. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2660